The Effect of Kinesthetic Learning Activities on Students' Speaking Skills: A Quantitative Study - Simamora, Joko Abadi; Iskandar; Sukardi Weda (International Journal of Language, Education, and Literature, 2025)
This research examines the effectiveness of Kinesthetic Learning Activities (KLA) in improving students' speaking skills at the Merchant Marine Polytechnic Makassar. This study applies an approach that is quantitative, adopting a pre-experimental, one-group pretest and posttest design to evaluate students' speaking performance before and after KLA implementation. A purposive sample of 24 second-year cadets was selected from a total population of 841 students. Data were acquired using pretests and posttests., in which students engaged in storytelling tasks assessed based on accuracy, fluency, and comprehensibility. Statistical analysis was performed using SPSS version 30, combining normality tests, paired sample t-tests, and Wilcoxon Signed-Rank tests to establish the significance of the data. The results indicate a significant improvement in students' speaking proficiency following the integration of kinesthetic learning activities. Pre-test scores revealed that most students were categorized as 'Fair' to 'Very Poor,' reflecting notable challenges in pronunciation, grammar, and fluency. However, post-test results demonstrated substantial progress, with a majority of students achieving higher proficiency levels. The Wilcoxon Signed-Rank Test confirmed a statistically significant difference between pretest and posttest scores, demonstrating KLA's effectiveness in improving students' oral communication skills. Consequently, the findings suggest that incorporating kinesthetic learning strategies into language instruction can be highly beneficial in maritime education. This research underscores the value of movement-based learning in vocational training and encourages further research to explore its long-term impact and applicability in structured academic settings.